An investor’s perspective on infectious diseases and their influence on market behavior - Wang, Yi-Hsien; Yang, Fu-Ju; Chen, Li-Je (Journal of Business Economics and Management, 2013)
Recently, increasing number of infectious diseases has swept the world. The outbreak of a contagious disease not only affects the health and lives of people but also causes economic growth to stagnate. Business in the biotechnology industry is closely related to infectious diseases but what exactly is the information value of the outbreak of infectious disease on biotechnology? This study investigates how such outbreaks can affect the performance of biotechnology stocks. In the past 10 years, major statutory infectious diseases in Taiwan have included ENTEROVIRUS 71, DENGUE FEVER, SARS and H1N1. The empirical results indicate that there is a significant abnormal return on company shares in Taiwan’s biotechnology industry because of statutory infectious epidemics. The relationship between the financial ratios of biotechnology companies and abnormal returns was analyzed as part of this research. The results show that the influence on R&D ratios, current ratios and assets are significant. Empirical findings reveal that the investors rationally measure operating conditions of the biotechnology companies during outbreaks of major infectious disease and adjust portfolio allocation accordingly.